Energy-efficient clock synchronization technique for IoT - Onyeka, Ezema Ernest (2019)
Energy saving and clock synchronization is critical to Internet of Things (IoT). Various energy efficient clock synchronization technique has been proposed recently. However, this technique (R-sync) utilizes a lot of energy and unsynchronized nodes exist in the technique, thereby making the algorithm not suitable for IoT Network. The technique obtains higher precision without considering the energy utilization. Unnecessary expenditure of energy leads to collision of sensor nodes. In this research, we proposed a Network Node ID (NN-I) technique for energy efficiency by applying the network node ID to avoid collision, ensure clock synchronization and energy saving. MATLAB was used for the simulation and the evaluation parameters for the simulation were the number of broadcast messages, the level of energy consumption and collision count. All experiment in the base work where used. The result of our research indicates a more improved clock synchronization and energy saving for IoT Network against the existing technique.